Factors Associated with Maternal Mortality in The Central General Hospital Dr. M. Djamil Padang 2020-2021 - Saddam, Fuad; Adnani, Syahredi (Fakultas Kedokteran Universitas Andalas, 2022)
Objective: To Know factors of cause maternal mortality at Dr. M. Djamil Central General Hospital in Padang during the period January 1st , 2020 - December 31st, 2021. Method: This study used a retrospective analytic design with a cross sectional study design and used logistic regression to know the role of factors maternal mortality. Determination of the sample using total sampling. Conducted review using a reference register book, medical records, for 2 years from January 1st, 2020 – December 31st, 2021 at the Department of Obstetrics and Gynecology, Dr. M. Djamil. Results: Selection of variables with chi-square bivariate analysis (p < 0.25) between maternal mortality with; obstetric emergency (p=0.039), comorbidities (p=0.587), maternal age (p=0.064), maternal education (p=0.920), parity (p=0.735), intensive care (p=0.000), and operative procedure. (p=0. 000). Multivariate analysis (p<0.05) to determine the most dominant factor; obstetric emergency (p=0.143), maternal age (p=0.269), intensive care (p=0.753) and operative procedures (p=0.000). Then test by removed the intensive care, and maternal age factors, the results of the operative procedure were obtained before (p=0.000, OR=161.158, 95% CI=12,343-2104,177) and after (p=0.000, OR= 133,368). Conclusion: obstetrics emergency, maternal age, intensive care, and operative procedure are factors that cause maternal mortality at Dr. M. Djamil Central General Hospital in Padang. Operative procedure is the most dominant factor causing 161 times greater maternal mortality.